Exceptional mechanical properties of AZ31 alloy wire by combination of cold drawing and EPT. (15th August 2020) - Shan, Zhaohui; Bai, Jing; Fan, Jianfeng; Wu, Hongfei; Zhang, Hua; Zhang, Qiang; Wu, Yucheng; Li, Weiguo; Dong, Hongbiao; Xu, Bingshe
Abstract: A 0.66 mm-diameter AZ31 alloy wire with ultimate tensile strength of 400 MPa and elongation of 28.5% was successfully prepared via the combination of cold-drawing and electropulsing treatment processing (EPT). Microstructure observation showed that the grain size of EPTed samples was refined to about 1 μm and the basal texture strength with maxima texture index was weakened to 7.18. EPT can significantly accelerate recrystallization by enhancing the mobility of dislocation and atomic diffusion due to the coupling of the thermal and athermal effects. Finally, uniform ultrafine-grained structure was obtained in the EPTed samples by static recrystallization completed in a very short time (30 s) at relatively low temperature (433 K).